THE ROLE OF RELIGION TEACHERS IN INSTALLING SOCIAL AWARENESS IN STUDENTS - Kamila, Rizqy; Saepuloh (ASWAJA: Jurnal Pendidikan dan Keislaman, 2023)
The role of religious teachers in instilling social awareness in students is a strong foundation in forming a young generation with character and morals. Religious teachers help create a better society, full of individuals who are responsible, caring, and able to contribute positively to social life. . The purpose of this research is to review the role of religious teachers in instilling social awareness in students at the Bakti Mulya High School, Bandung Regency. The research method used is descriptive qualitative with the selection of research subjects using purposive sampling. Data collection was carried out through observation, interviews, and documentation, with research subjects including school principals, student affairs staff, Islamic Religious Education teachers, and students. Data analysis is carried out through the stages of data collection, data reduction, data display and verification. The results of the research show that the role of religious teachers in instilling social awareness in students at Bakti Mulya High School, Bandung Regency is reflected in attitudes of mutual respect, cooperation and tolerance among students, building a harmonious and inclusive school community. This means that the school environment has positive values ??and supports the process of internalizing social values ??in students. This success was verified through a data assessment rubric which included observation, interviews and documentation, showing that the teacher's role was able to form students who had a high social sense. From the results of this research, it can be concluded that the role of teachers is very important in cultivating social awareness in students.